1982
DOI: 10.1128/iai.38.1.147-156.1982
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus mutans Genes That Code for Extracellular Proteins in Escherichia coli K-12

Abstract: Chromosomal DNA from Streptococcus mutans 6715 (serotype g) was cloned into Escherichia coli K-12 by using the cosmid pJC74 cloning vector and a bacteriophage X in vitro packaging system. Rabbit antiserum against S. mutans extracellular proteins was used for immunological screening of the clone bank. Twenty-one clones produced weak to strong precipitin bands around the colonies, but only after the X c1857 prophage was induced by being heated to lyse the E. coli cells. None of the clones expressed enzyme activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 44 publications
1
63
0
Order By: Relevance
“…Both proteins were principally found in the cytoplastn or associated with the cytoplasmic membrane, indicating that the proteins are not secreted into the periplasmic space. However, cloned protein PI and Spa A were able to penetrate the cytoplasmic metnbrane and were predotninantly found in the periplastnic space (6,7). Two different explanations can be given to these observations: either the protein is synthesized in E. coli in high amounts resulting in an aggregation of the protein which prevents the passage through the cytoplastnic tnembrane or the lack of a post-transcriptional procedure in E. eoli.…”
Section: Resultsmentioning
confidence: 99%
“…Both proteins were principally found in the cytoplastn or associated with the cytoplasmic membrane, indicating that the proteins are not secreted into the periplasmic space. However, cloned protein PI and Spa A were able to penetrate the cytoplasmic metnbrane and were predotninantly found in the periplastnic space (6,7). Two different explanations can be given to these observations: either the protein is synthesized in E. coli in high amounts resulting in an aggregation of the protein which prevents the passage through the cytoplastnic tnembrane or the lack of a post-transcriptional procedure in E. eoli.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have shown that recombinant SpaA protein expressed by the S. sobrinus spaA gene cloned into E. coli cells was predominantly localized to the periplasm of the E. coli cells [7]. In this communication, we analyze using TnphoA the sequences needed to mediate this periplasmic localization of the S. sobrinus SpaA protein.…”
Section: Introductionmentioning
confidence: 97%
“…The virulence of the mutans streptococci depends on extracellular expression of virulence determinants including glucosyltransferases and surface protein antigens. A family of proteins designated by di¡erent laboratories as antigen B [3], antigen I/II [4], SpaP1 [5] or PAc [6] expressed by Streptococcus mutans and SpaA [7] or PAg [8] protein expressed by Streptococcus sobrinus are important virulence determinants for the mutans streptococci. Both of these proteins as well as a similar protein produced by Streptococcus sanguis [9] have been shown to interact with salivary agglutinins to facilitate colonization of enamel surfaces [10] or interact with £uid phase agglutinin to mediate cell to cell aggregation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Proteins closely associated with the cell wall appear to facilitate the colonization of enamel surfaces by S. sobrinus and other members of the mutans streptococci. S. sobrinus cells express a major high molecular mass protein called SpaA [2,3]. The SpaA protein also has been referred to as PAg [4].…”
Section: Introductionmentioning
confidence: 99%
“…Proteins antigenicaUy similar to the SpaA protein have been shown to be produced by all of the serotypes of the mutans streptococci with the exception of serotype b [2,7,8] and also by Streptococcus sanguis [9]. Sequence analysis of the spaA gene indicates that the mature SpaA protein has a M r of 160500 [10].…”
Section: Introductionmentioning
confidence: 99%